Developing a holistic approach for medical injuries compensation: the strength of community responsibilities - Mohd Najid, Khadijah; Jahn Kassim, Puteri Nemie (USIM Press, Universiti Sains Islam Malaysia, 2018)
The efficiency and relevancy of the tort system in offering adequate redress for victims of medical injuries has become a global concern. The tort system’s emphasis on fault, personal blame and individual responsibility has not been successful in functioning as a mechanism that is able to enhance patient safety as a whole, as it triggers negative implications such as inadequate monetary compensation, overburdened healthcare providers, and consequently, ineffective deterrence towards neglectful conduct. The flaws in the tort system had prompted the move from a system that is based on individual responsibility towards a no-fault system that is based on collective responsibilities. Founded on the ideals of distributive justice, the no-fault system shifts the focus away from individual fault and places more emphasis on victim’s rehabilitation. It further leads to an establishment of a systematic injury prevention system by enhancing co-operative community support as well as educational reform. The attributes of the no-fault system, is seen to be in line with the Islamic system of diyah, which accentuates the role of the community as central to the administration of justice, and places mutual responsibility to provide assistance for victims of medical injuries within the community. The system of diyah further represents a holistic method of economic empowerment which enables the setup of a multidimensional welfare system in caring for the disadvantaged in the community. The strength of community responsibilities should not be overlooked as it has the power to be a central driving force towards a good healthcare system and a prosperous society.